DEPENDENCE OF POLARON MASS ON OXYDEN CONTENT IN Hg-1201 CUPRATE - Saburova, Gulnoza Gulumbaevna; Yavidov, Bahram Yangibaevich (SCIENCE and SOCIETY, 2026)
In this paper, the dependence of the polaron mass on the oxygen content in Hg-1201 cuprate is studied. The bipolaron model of high-temperature superconductivity is chosen as the research model. Taking into account the dependence of the superconducting critical temperature, the size of the unit cell of the crystal lattice, and the anisotropy coefficient of the charge carrier mass on the oxygen content in Hg-1201 cuprate from the experiment, the dependence of the polaron mass on the oxygen content is found. The theoretically obtained polaron mass values are compared with the experiment. It is shown that the theory is consistent with the experiment at the optimal oxygen content.
Keywords: Hg-1201; (bi)polaron; superconductivity; Bose-Einstein condensation; mass